Pengaruh Lembaga Pelatihan Kerja Terhadap Angka Pengangguran di Indonesia - Rena Maretha Sari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Fuel oil (BBM) is a commodity whose price is determined by the state. It has been approximately 3 months since fuel oil prices experienced an increase due to the increasing burden of energy subsidies. This has had a significant impact on almost all Indonesian people, which has also been exacerbated by the impact after the pandemic. Based on this case, this article was written with the aim of providing more in-depth information regarding the impact of the swelling burden of energy subsidies which influenced the increase in fuel prices after the pandemic event due to Covid-19 in Indonesia. The literature review research method was used in this research by identifying and evaluating the results of research and ideas that had previously been produced by other researchers. The results of the research found that the increase in the subsidy burden had an effect on the increase in fuel oil (BBM) prices which then had an impact on the prices of goods and services which also increased following the increase in fuel oil (BBM) prices.